The Impact of Insecticide Pre-Exposure on Longevity, Feeding Succession, and Egg Batch Size of Wild Anopheles gambiae s.l. - Grace Msangi; Moses I. Olotu; Aneth M. Mahande; Anitha Philbert; Eliningaya J. Kweka (Journal of Tropical Medicine)
Background. Insecticide resistance among the vector population is the main threat to existing control tools available. The current vector control management options rely on applications of recommended public health insecticides, mainly pyrethroids through long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS). Regular monitoring of insecticide resistance does not provide information on important factors that affect parasite transmission. Such factors include vector longevity, vector competence, feeding success, and fecundity. This study investigated the impacts of insecticide resistance on longevity, feeding behaviour, and egg batch size of Anopheles gambiae s.l. Method. The larval sampling was conducted in rice fields using a standard dipper (350 ml) and reared to adults in field insectary. A WHO susceptibility test was conducted using standard treated permethrin (0.75%) and deltamethrin (0.05%) papers. The susceptible Kisumu strain was used for reference. Feeding succession and egg batch size were monitored for all survivors and control. Results. The results revealed that mortality rates declined by 52.5 and 59.5% for permethrin and deltamethrin, respectively. The mortality rate for the Kisumu susceptible strain was 100%. The survival rates of wild An. gambiae s.l. was between 24 and 27 days. However, the Kisumu susceptible strain blood meal feeding was significantly higher than resistant colony (t = 2.789, df = 21, P=0.011). Additionally, the susceptible An. gambiae s.s. laid more eggs than the resistant An.gambiae s.l. colony (Χ2 = 1366, df = 1, P≤0.05). Conclusion. It can, therefore, be concluded that the wild An. gambiae s.l. had increased longevity, blood feeding, and small egg batch size compared to Kisumu susceptible colonies.